Consumer Protection Against Skincare Trade Not Yet Licensed By Bpom Through E-Commerce - Hidayati, Hidayati; Aripin, Aripin (Jurnal Locus Penelitian dan Pengabdian, 2024)
Cosmetics are a tool of women's beauty. Skincare Cream is one of the cosmetics that changes the appearance to confidence. Trade through E-commerce is a form of technological and information advancement, but it is abused by unlicensed skincare cream traders. This study aims to find out about the skincare trade without a distribution permit and consumer protection in terms of supervision and enforcement of skincare by the Food and Drug Supervisory Agency which is sold through e-commerce. The method used is normative juridical which focuses on applicable positive legal norms, legal doctrines, and other legal literature. The results of the study show that based on Law Number 8 of 1999 concerning Consumer Protection through the Food and Drug Supervisory Agency, several preventive measures have been taken to protect the public from skincare creams without a distribution permit through e-commerce through premarket and post -market. In handling the mushrooming skincare trade, the Food and Drug Supervisory Agency will also test its safety, efficacy, and quality and collaborate with the police and government agencies to conduct cyber patrols.